Middle-Aged and Older Caregivers’ Loneliness and Neighborhood Disorder: The Buffering Role of Social Support - Seungjong Cho (Health & Social Work, 2026)
Abstract This study explores the relationship between perceived neighborhood disorder and loneliness among middle-aged and older caregivers. It also examines whether social support buffers the potential negative influence of neighborhood disorder on loneliness. Using data from the 2018 Health and Retirement Study (N = 578), this study estimated relationships using ordinary least squares regression. Loneliness was measured using an 11-item scale. Perceived neighborhood disorder was measured with an eight-item scale covering physical and social disorder. Social support was measured via a 12-item scale of positive social interactions. Respondents who experienced higher levels of perceived neighborhood disorder show higher levels of loneliness (p < .001). Social support was significantly associated with reduced loneliness (p < .001). However, there was no significant interaction effect between neighborhood disorder and social support (p = .495), indicating that social support did not buffer this association. Among covariates, only self-rated health was significantly related to loneliness (p < .001). These findings highlight the importance of addressing neighborhood stressors to mitigate loneliness in this vulnerable population. While social support is a powerful direct resource, community-level interventions may be necessary to address the harms of neighborhood disorder.